1997
DOI: 10.1007/s11837-997-0025-4
|View full text |Cite
|
Sign up to set email alerts
|

Predicting microstructure and microsegregation in multicomponent alloys

Abstract: OverviewAccurate predictions of microstructure and microsegregation in metallic alloys are highly important for applications such as process optimization and alloy development. This article gives an overview of the methods developed during the past 30 years for solidification simulation on a microscopic scale, with a special emphasis on multicomponent alloys. Analytical approaches as well as advanced numerical models coupled with greatly simplified phase diagrams and thermodynamically calculated phase diagrams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 85 publications
(110 reference statements)
0
26
0
Order By: Relevance
“…Kraft and Chang [13] summarized a variety of modeling work on microsegregation despite ongoing development. The existing modeling approaches consist of numerical and analytical solutions.…”
Section: Microsegregationmentioning
confidence: 99%
See 1 more Smart Citation
“…Kraft and Chang [13] summarized a variety of modeling work on microsegregation despite ongoing development. The existing modeling approaches consist of numerical and analytical solutions.…”
Section: Microsegregationmentioning
confidence: 99%
“…The Gibbs free energy change is the most popular thermodynamic criteria. At a given temperature, the Gibbs energy change (∆G) for the reaction is given by Equation (13).…”
Section: Thermodynamics Of Inclusion Formationmentioning
confidence: 99%
“…More recently the use of thermodynamic databases in steel microsegregation models has become popular [153][154][155][156] and kinetic effects have also been incorporated into models .111,157-163) Nevertheless, adding such complexity into macrosegregation models often comes at great computational expense, and consequently there has been some development of rapid microsegregation models for incorporation into macromodels. 164) For those seeking further details on microsegregation models, the review by Kraft and Chang 165) is a useful starting point.…”
Section: Microsegregation Modelsmentioning
confidence: 99%
“…The main limiting factor of all existing mathematical micro-segregation models consists in lack of available thermodynamic and kinetic data, especially for systems of higher orders. There is also little experimental data to check the models (Kraft & Chang, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there is a strong industrial need to investigate and simulate more complex alloys because nearly all current commercial alloys have many components often exceeding ten elements. Moreover, computer simulation have shown that even minute amounts of alloying elements can significantly influence microstructure and micro-segregation and cannot be neglected (Kraft & Chang, 1997). Dendritic crystallisation is general form of crystallisation of salts, metals and alloys.…”
Section: Introductionmentioning
confidence: 99%